KEBERHASILAN PRAKTIKUM SISWA SMK NEGERI 5 PALU DITINJAU DARI KETERLAKSANAAN RENCANA PELAKSANAAN PEMBELAJARAN - Muhtar, Muhtar (JSTT, 2015)
This reseacrh is action-research which adapted from Wenning’s Model of Inquiry Lab (2005). The objective of this research is to describe the application of lesson plan to practice in SMK. The focus of the study is on the subject of motion and force of the motorcycle components. Application of the practice to be guided lesson plan described by using Riel’s action-research (2013). This research have a collaborative feature which is between the researcher with the relevant educator friends or source experts participated on the observation as the critical friend. The technique to collect of the datas include observations, interviews, tests and analysis of documents. The technique of data analysis in this research is descriptive analysis of comparative and critical analysis techniques. The results showed that enforceability of lesson plan (RPP) in cycle 1 is enough category, cycle 2 is good category and cycle 3 is very good category. The aspects of attitude assessment cycle 1 is enough category, cycle 2 is enough category and cycle 3 good category. Aspects of skills and completeness portfolio cycle 1 is not good enough category, cycle 2 is enough category and cycle 3 enough category. The description of the practicum activities goes well according to procedures on the practicum module and the students were able to find the concept based on the practicum activities. Based on the result of this research, it can be concluded that the prepartion, implementation and the factor is influential in implementing the lesson plan practice on the subject of motion and force of the motorcycle components in SMK implemented as planned with good results.